Conceptualising regional skills ecosystems: Reflections on four African cases. (22nd November 2021) - Wedekind, Volker; Russon, Jo‐Anna; Ramsarup, Presha; Monk, David; Metelerkamp, Luke; McGrath, Simon
Abstract: In this article we address the debate on regional skills formation systems in Africa. We draw on the social ecosystems model (SEM) developed by Hodgson and Spours to analyse data from four case studies that reflect the complexities of African economies, rural and urban, formal and informal. The SEM model helps us focus on the three dimensions of a strong skills ecosystem: collaboration between a range of actors, key institutions and system leaders within the region (the horizontal); top‐down policies, regulations, and funding streams that enable or constrain the regional skills ecosystem (the vertical); and the points where these two interact, often through mediation activities. In the case of the last of these three, our cases point to the importance of nurturing organisations which can provide SEM leadership, particularly in more fragile ecosystems. Yet, in none of the cases, are public vocational institutions playing the strong anchor role envisaged in the model. The significance of the paper lies in three ways it develops the SEM in relation to regional skills ecosystems. First, we problematise the notion of a facilitatory state and place it within wider national and global webs of power. Second, we insist that the local or regional is always embedded in and networked into myriad national and international levels. This requires a more complex understanding of how social skills ecosystems operate. Third, the notion of an anchor institution requires further elaboration. In most social ecosystems these institutions need to be built or strengthened and a clearer understanding is required of the processes of institutionalisation and what mechanisms make it possible to build this capacity and sustain it over time.